INSIGHTS INTO WEALTH MANAGEMENT PRACTICES AND FINANCIAL MARKET DYNAMICS - Jakhar, Aarush; Bhalerao, Amol; Padroo, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
Wealth management has become an essential part of personal and institutional financial planning, especially in an economy where market fluctuations, inflation, and global events constantly influence investment outcomes. With increasing financial awareness, individuals now seek structured investment strategies that help them grow and protect their wealth. This research paper examines the concept of wealth management and explains how financial markets operate in today’s interconnected world. The study focuses on investment instruments, risk assessment, financial planning, market behavior, and the impact of technology on investment decisions. Information has been gathered from books, financial journals, official reports, and credible online sources. Graphs, tables, and conceptual analysis are used to highlight patterns in investor preferences and market performance. The overall findings indicate that successful wealth management requires consistent planning, a balanced portfolio, understanding of market trends, and the ability to manage financial risks effectively.